The Relationship between Emotional Intelligence and Mathematical Competency among Secondary School Students - Nor, Nurul Adibah Khairiyah Mohd; Ismail, Zaleha; Yusof, Yudariah Mohammad (Journal on Mathematics Education, 2016)
Anxiety towards mathematics among secondary school students have been reported. Anxiety creates strong negative emotions and can hinder a person's cognitive, learning and academic performance. Fear of mathematics came early in the educational process and if this is not handled properly, it will negatively affect the students to adulthood. In learning mathematics, emotional intelligence (EI) impacts on how a person deals with emotions, mathematics and the general self-regulations strategies that the person adopts. A study was carried out to access secondary students’ EI and their mathematical competency (MC). The EI was tested using an EI questionnaire for adolescents (IKEM-R/MEQI) consisting of 7 domains, while the MC was tested using selected questions from PISA (Programme for International Student Assessment) 2012 released items. Analysis shows that EI predict significantly students MC, but with low correlational value. Most of the respondents have moderate level of EI in all 7 domains whereby self awareness and self-regulation are the two domains with lowest scores. On the other hand, most of the students’ MC are poor. This particular research shows that EI is not a good predictor of MC which contradicts other reports. However it is suggested that the data collection can be improved by examining students’ EI while they are engaging in activities that call for MCs rather than doing it before or after the tasks. Keywords: Emotional Intelligence (EI), emotion, Mathematical Competency (MC), PISA (Programme for International Student Assessment), anxiety DOI: http://dx.doi.org/10.22342/jme.7.2.3534.91-100